Modeling Parkinson’s Disease in Drosophila: What Have We Learned for Dominant Traits? - Xiong, Yulan; Yu, Jianzhong (Frontiers in Neurology, 2018)
Parkinson’s disease (PD) is recognized as the second most common neurodegenerative disorder after Alzheimer’s disease. Unfortunately, there is no cure or proven disease modifying therapy for PD. The recent discovery of a number of genes involved in both sporadic and familial forms of PD has enabled disease modeling in easily manipulable model systems. A variety of model systems have been developed to study the pathobiology of PD and provided tremendous insights into the molecular mechanisms underlying dopaminergic neurodegeneration. Among all the model systems, the power of Drosophila has revealed many genetic factors involved in the various pathways, as well as provided potential drug targets for therapeutics. This review focuses on Drosophila models of PD, with emphasis on how Drosophila models have provided new insights into the mutations of dominant genes causing PD and what are the convergent mechanisms.